Women's Career Jacket Design: Stylish and Practical Look for Motorcyclists in Bandung - Dea Athiyyah Khalishah; Edwin Buyung; Muchlis (Judikatif: Jurnal Desain Komunikasi Kreatif, 2025)
This research aims to design a career women's jacket that supports motorbike riding activities in Bandung. Using the User-Centered Design (UCD) method, this research combines observation, in-depth interviews, and questionnaires to identify user needs. Observations show problems with the comfort, protection and appearance of the jackets currently used. Interviews with career women revealed a preference for weather-resistant and comfortable materials, sleek and fashionable designs, and additional features such as practical pockets and air space. The final design incorporates weather-resistant materials, stylish cuts, and additional features for comfort and safety. This jacket is expected to support the mobility and lifestyle of career women in Bandung, combining professionalism, comfort and protection.